Simvastatin impairs the induction of pulmonary fibrosis caused by a western style diet: a preliminary study. Issue 11 (25th August 2015) - Kruzliak, Peter; Hare, David L.; Zvonicek, Vaclav; Klimas, Jan; Zulli, Anthony
Abstract: The role of an atherogenic diet in causing pulmonary fibrosis has received little attention and simvastatin has been shown to reduce pulmonary fibrosis in animal models. To determine if an atherogenic diet can induce pulmonary fibrosis and whether simvastatin treatment is beneficial by up‐regulating heat shock protein 70 and 90. New Zealand white rabbits ( n = 15) were divided: Group 1 (control); Group 2 (MC) received a normal rabbit diet with 1% methionine plus 0.5% cholesterol (atherogenic diet). Group 3 received the same diet as the MC group plus 5 mg/kg/day simvastatin orally (MCS). After 4 weeks, the lungs were collected and analysed. Picrosirus red staining of lung interstitial collagen content showed that the atherogenic diet increased fibrosis 2.9‐fold ( P < 0.05), bronchiole adventitial collagen was increased 2.3‐fold ( P < 0.05) and bronchiole epithelium was increased 34‐fold ( P < 0.05), and simvastatin treatment severely reduced this effect ( P < 0.05). Western blot analysis showed that the atherogenic diet significantly reduced lung Hsp70 protein by 22% ( P < 0.05) and Hsp90 protein by 18% ( P < 0.05) and simvastatin treatment did not affect this result. However, aortic hyper‐responsiveness to vasoconstrictors (angiotensin II and phenylephrine) were markedly reduced by simvastatin treatment. We report that an atherogenic diet stimulates pulmonary fibrosis and reduces lung Hsp70/Hsp90 protein concentration. Simvastatin impairs this by mechanisms unrelated to Hsp70/Hsp90, but possibly a reduction in angiotensin II receptor or alpha adrenergic receptor pathways. These results could have implications in idiopathic pulmonary fibrosis.